Technology and the Evolution of Civil Law: Implications of Cryptocurrency Transaction Regulation - Wahyuddin, Fitrah; Sudirman, Sudirman; Umar, Wahyudi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research investigates the regulatory implications of cryptocurrency transactions in the context of the evolution of civil law, including consumer protection, prevention of illegal activities, and maintenance of financial market integrity. The background of the research refers to the economic paradigm shift towards digital assets such as cryptocurrencies, which has changed the global financial transaction landscape. This research method involves a combined approach between civil law analysis, a literature study on blockchain technology, and a review of the latest regulations related to cryptocurrencies in Indonesia. The results show that the evolution of technology in cryptocurrencies has presented new challenges to conventional civil law. The unclear legal status of cryptocurrencies, security risks, and potential illegal use are significant concerns. The regulatory implications on cryptocurrency transactions in Indonesia illustrate the government's efforts to accommodate innovation while protecting the public interest. Some recommendations include a more collaborative approach between the government, the industry sector, and legal institutions to develop a regulatory framework that fits the characteristics of these technologies.